Versatility of endoaortic balloon occlusion device for less invasive management of complex and reoperative cardiac cases. Issue 7 (18th June 2019) - Agnino, Alfonso; Albano, Giovanni; Ruggieri, Vito G.; Roscitano, Claudio; Graniero, Ascanio; Villari, Nicola; Giroletti, Laura; Anselmi, Amedeo
Abstract: Heart Teams are increasingly confronted with decision‐making in anatomically and clinically complex surgical candidates. Herein, we discuss the versatility of the endoaortic occlusion device (Intraclude; Edwards Lifesciences Inc) for the management of a various array of complex primary and reoperative cardiac cases. Three clinical scenarios are illustrated (ascending aortic pseudoaneurysm, mitral valve surgery after previous CABG, extensive thoracic aortic surgery with continuous visceral perfusion), suggesting the effectiveness of the patient‐specific strategy to minimize operative morbidity. Evolution of surgical techniques needs to be considered in decision‐making among alternative treatment strategies.